Enriching individual absorptive capacity - Tian, Amy; Soo, C. (Emerald, 2018)
© 2018, Emerald Publishing Limited. Purpose: The purpose of this paper is to offer an understanding of the development and consequence of absorptive capacity (AC) at the individual level of analysis. The authors assess how perception of organizational commitment to learning and intrinsic motivation affects individual potential AC, and employee creativity and job performance as the key outcomes of individual AC. Furthermore, the authors examined the dual role of realized AC as a mediator in the potential AC-creativity relationship, and a moderator on the creativity-job performance relationship. Design/methodology/approach: This paper draws from 125 paired supervisor-employee survey data, where supervisors rated subordinates’ creativity and job performance. Hierarchical regression was used to test the proposed hypotheses. Findings: The results confirm that both perception of organizational commitment to learning and intrinsic motivation contribute to the development of individual potential AC (above and beyond extrinsic motivation). Individual realized AC mediated the potential AC-creativity relationship. Employee creativity was positively related to job performance. Research limitations/implications: This study speaks directly to the question of how an organization can encourage its employees to absorb new knowledge, and the benefits of employee learning activities on their creativity and job performance. Originality/value: This is one of the first studies to offer a more nuanced understanding of the development and consequences of individual AC – a level of analysis has been lack of empirical studies. It further point out how individual characteristic and perceptions can influence their learning capacity, and in turn, their performance.